PERILAKU HEDONISME MAHASISWA DI TRANS STUDIO MALL MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study aims to determine the factors that influence the student's hedonism, the forms of hedonism, and the impact on students' hedonism in Trans Studio Mall Makassar. This research uses a type of qualitative research with a sociological approach. The data collection methods used are observations, interviews, and documentation. The technique of data processing and analysis is carried out through three phases: data reduction, data presentation, and conclusion withdrawal. The results of this study show that: (1) internal factors of students hedonism, such as happy with the crowd, shopping and want to enjoy the youth and external factors such as parents who familiarize their children living luxury since childhood, peers, social environment; (2) the behavioral forms of student hedonism demonstrated by shopping and hanging out in the cafe; (3) positive impacts of student hedonism, among others, desires, and desires, can reduce and suppress the level of stress that exists in the individual, increasing the confidence, have the motivation to achieve the desire as well as the negative impact of the consumptive, extravagant, follow-up, want to get recognition and waste of time.